Visual Studies: Identification of Cangkuang Temple As a Heritage Relic of Ancient Sunda Kingdom with Juxtaposing Technique - Rahmadi Rahmadi; Aldi M Fitrah (JOMANTARA, 2021)
West Java has various relics of buildings and ancient artifacts that have the characteristics of buildings based on Hinduism, Buddhism and other older cultures. One of these remains is the Cangkuang Temple (8M) located in Garut, West Java. This temple is a Hindu-style temple, and is believed to be a relic of the Ancient Sundanese Kingdom. However, what is interesting about this Cangkuang Temple building is that it has quite different building characteristics from other sacred buildings of the ancient Sundanese people that were around the same era and in the surrounding area. This Cangkuang Temple has some similarities from the characteristics of the buildings generally from Ancient Sundanese, but has quite a few different distinct building features. This makes the question of whether Cangkuang Temple is really a relic from Ancient Sundanese Kingdom or by another kingdom in the different era. Therefore, in this research, the writer tries to raise the issue of these characteristics and differences. In the process, the writer compares the photo of the temple and the comparator with the Diptych and Triptych technique to identify the similarities and differences of the temples as objects. The research methodology used in this reseras is a descriptive qualitative visual study, with the data collection methods used are field observations, literature reviews and interviews. The objects that are observed are the sacred buildings of the Sundanese people of the same era and those in the surrounding area. In the end, after the photos are juxtaposed, they will be further validated to get the final conclusion. This research also includes comparisons with Gedong Songo Temple which complements the existing comparisons between the buildings of the Tarumanegara (Batujaya), Ancient Sundanese (Bojongmenje) and Galuh / Kalingga / Medang (Gedong Songo) era’s building to see their characteristics comparison.